An aminoglycoside antibiotic-modified tin dioxide perovskite solar cell

By modifying tin dioxide as the electron transport layer with aminoglycoside antibiotics, the dispersion, defects and interface problems of the SnO2 electron transport layer are solved, and the photoelectric conversion efficiency and stability of perovskite solar cells are improved.

CN115101671BActive Publication Date: 2025-05-02SHANXI JUNLIANG OPTOELECTRONICS TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210610933.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-05-31
Publication Date
2025-05-02
Estimated Expiration
2042-05-31

AI Technical Summary

Technical Problem

The existing SnO2 electron transport layer has problems with dispersion, lattice internal defects, interface defects and poor perovskite crystallinity, which affects the photoelectric conversion efficiency and stability of perovskite solar cells.

Method used

Aminoglycoside antibiotics are used to modify tin dioxide as the electron transport layer, and the interaction between SnO2 nanocrystals is weakened by modifying the macromolecular structure, improving the uniformity and smoothness of the film, and passivating defects inside the SnO2 lattice through ion bonding to reduce interface defects.

Benefits of technology

The stability and conductivity of the SnO2 electron transport layer are improved, the photoelectric conversion efficiency of perovskite solar cells and the short-circuit current of the device are improved, non-radiative recombination is reduced, and the crystallinity of perovskite is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115101671B_ABST
    Figure CN115101671B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of perovskite solar cells, and is a perovskite solar cell containing aminoglycoside antibiotics modified with tin dioxide. The aminoglycoside antibiotics with multiple functional groups significantly improve the dispersibility of the tin dioxide colloidal solution, passivate the defects inside the tin dioxide lattice, and obtain an electron transport layer with excellent performance. On the other hand, the interface defects between the tin dioxide electron transport layer and the perovskite layer are significantly reduced. The guanidine group of the aminoglycoside antibiotic promotes the growth of the perovskite crystal, and the crystal size is significantly increased. The photovoltaic conversion efficiency (PCE) and device stability of the solar cell finally prepared are significantly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of perovskite solar cells, and in particular to a tin dioxide electron transport layer modified by aminoglycoside antibiotics and a preparation method of a perovskite solar cell thereof. Background Art

[0002] Perovskite solar cells have been rapidly developed in recent years due to their advantages such as low production cost, simple preparation process, high photoelectric conversion efficiency, and the ability to be made into flexible and semi-transparent devices, bringing major innovations to solar energy technology. Therefore, the research and development of perovskite solar cells is of great significance to the large-scale utilization of solar energy and sustainable development strategies. Today, the highest photoelectric conversion efficiency (PCE) of perovskite solar cells (PSCs) has reached 25.7%, which is comparable to commercial crystalline silicon solar cells.

[0003] PSCs are mainly composed of electrodes, electron transport layers (ETLs), perovskite layers, and hole transport layers. Among them, the electron transport layer plays a very important role in perovskite solar cells. A good electron transport layer material should have high electron injection efficiency, and must also prevent electrons and holes from recombination at the interface and have good optical transmittance in the visible light range, thereby reducing light energy loss. At present, many n-type metal oxides such as TiO 2 , ZnO, SnO 2 etc. have been used as ETL. 2 Compared with the two ETLs of SnO and ZnO, 2 It shows better optical and electrical properties, better matching with the energy band of perovskite and good environmental stability, which is very suitable for the application of perovskite solar cells. However, tin oxide also has many inevitable disadvantages. First, SnO 2 Nanoparticles are unstable due to the existence of van der Waals interactions between particles and are prone to form large aggregates. 2 The lattice may have oxygen and tin vacancies (V O 、V Sn ), oxygen and tin gap (O i Sn i ) and oxygen and tin antisite defects (Sn O , O Sn ). Although oxygen vacancies and tin interstitials form shallow donor levels near the conduction band, SnO 2 The film has n-type characteristics, but from the perspective of the device, if too many charge trap states exist in the electron transport layer, it will lead to an increase in the non-radiative recombination of the entire device and hinder the charge transport process. 2 A large number of defects may form at the perovskite interface, and the perovskite2 The surface crystallinity is poor.

[0004] In order to overcome SnO 2 Solution dispersion problem, SnO 2 Defects in the lattice, SnO 2 In order to solve the defect problem at the interface of tin dioxide / perovskite and the crystallinity problem of perovskite, the present invention proposes a preparation method of a tin dioxide electron transport layer modified with aminoglycoside antibiotics and a perovskite solar cell thereof. Summary of the invention

[0005] The purpose of the present invention is to overcome the SnO 2 Solution dispersion problem, SnO 2 Defects in the lattice, SnO 2 The defect problems at the interface of perovskite and the crystallinity problems of perovskite provide a perovskite solar cell with simple process, excellent photoelectric conversion efficiency, outstanding stability and almost no hysteresis effect.

[0006] The technical solution adopted by the present invention is: a perovskite solar cell containing aminoglycoside antibiotics modified with tin dioxide, wherein the aminoglycoside antibiotics modified with tin dioxide SnO 2 As an electron transport layer of a perovskite solar cell, the method for preparing a perovskite solar cell is performed according to the following steps S1, pre-treating a transparent conductive glass substrate;

[0007] S2, spin coating the aminoglycoside antibiotic modified tin dioxide precursor solution on the pretreated transparent conductive glass substrate in step S1, and then heat treating it at 150° C. for 30 min to form an electron transport layer on the transparent conductive glass substrate; S3, spin coating and depositing a perovskite active layer on the surface of the electron transport layer;

[0008] S4, spin coating a hole transport material on the surface of the perovskite active layer to obtain a hole transport layer;

[0009] S5. Vapor-depositing a metal electrode on the hole transport layer to obtain a perovskite solar cell containing aminoglycoside antibiotic-modified tin dioxide as an electron transport layer, i.e., an aminoglycoside antibiotic-modified tin dioxide perovskite solar cell.

[0010] The aminoglycoside antibiotic in step S2 is a mixture of one or more of streptomycin sulfate, gentamicin sulfate and kanamycin sulfate.

[0011] In step S2, the aminoglycoside antibiotic modified tin dioxide precursor solution is obtained by fully mixing and shaking the aminoglycoside antibiotic aqueous solution and the tin dioxide colloidal aqueous dispersion; wherein the aminoglycoside antibiotic aqueous solution is a solution formed by dissolving 7 mmol of aminoglycoside antibiotics in 1 mL of deionized water, the tin dioxide colloidal aqueous dispersion is formed by uniformly mixing deionized water and tin dioxide colloid in a volume ratio of 4:1, and the volume ratio of the aminoglycoside antibiotic aqueous solution and the tin dioxide colloidal aqueous dispersion is 1:12 when mixed; the aminoglycoside antibiotic modified tin dioxide precursor solution is spin-coated on the pretreated transparent conductive glass substrate in step S1, the spin coating rate is 4000r / min, and the spin coating time is 30s.

[0012] In step S3, a two-step spin coating method is used when spin coating the perovskite active layer on the surface of the electron transport layer. The specific steps are as follows:

[0013] S31, 1.3 mmol lead iodide PbI 2 The precursor solution was dissolved in 1 mL of a mixed solvent of N, N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) to prepare a precursor solution, wherein the volume ratio of DMF to DMSO in the mixed solvent of N, N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) was 19:1. The precursor solution was spin-coated on the surface of the electron transport layer at a spin-coating rate of 1500 r / min for 30 s and heat-treated at 70°C for 1 min to prepare PbI 2 S32, formammonium iodide FAI, methylammonium bromide MABr, and methylammonium chloride MACl were mixed in a mass ratio of 10:1:1, and then dissolved in 2 mL of isopropanol solution to form a MA solution with a concentration of 72 mg / mL. x FA 1-x Br y I z Cl 1-y-z solution, x, y, z are the number of atoms in the molecule; MA x FA 1- x Br y I z Cl 1-y-z The solution was spin-coated on PbI obtained by S31 2 The film is heat treated at 80-120° C. for 10-60 min to obtain a perovskite film. In step S4, spin coating a hole transport material on the surface of the perovskite active layer to obtain a hole transport layer comprises the following steps

[0014] S41, dissolving 540 mg of Li-TFSI in 1 mL of acetonitrile solution, shaking thoroughly, to obtain a Li-TFSI acetonitrile solution; dissolving 720 mg of 2,2,7,7′-tetrakis[N,N′-di(4-methoxyphenyl)amino]-9,9′-spirobifluorene in 1 mL of chlorobenzene, shaking thoroughly, to obtain a 2,2,7,7′-tetrakis[N,N′-di(4-methoxyphenyl)amino]-9,9′-spirobifluorene chlorobenzene solution;

[0015] S42. Sequentially add 18 μL of lithium bis(trifluoromethanesulfonic acid) imide acetonitrile solution and 29 μL of 4-tert-butylpyridine to the 2,2,7,7′-tetrakis[N,N′-di(4-methoxyphenyl)amino]-9,9′-spirobifluorene chlorobenzene solution, and shake thoroughly to obtain a 2,2,7,7′-tetrakis[N,N′-di(4-methoxyphenyl)amino]-9,9′-spirobifluorene mixed solution; S43. Spin-coat the 2,2,7,7′-tetrakis[N,N′-di(4-methoxyphenyl)amino]-9,9′-spirobifluorene mixed solution on the surface of the perovskite active layer at a spin-coating rate of 4000 r / min and a spin-coating time of 30 s to form a hole transport layer.

[0016] A metal electrode is evaporated on the hole transport layer. The metal electrode material is Ag, Au or Al. A vacuum coating machine is used to evaporate a silver electrode on the surface of the hole transport layer using a conventional thermal evaporation process. The evaporation rate is 0.1 nm / s and the area of ​​the metal electrode is 0.04 cm 2 .

[0017] The thickness of the electron transport layer is 30-40 nm, the thickness of the perovskite layer is 480-500 nm, the thickness of the hole transport layer is 150-180 nm, and the thickness of the metal electrode is 100 nm.

[0018] The transparent conductive glass substrate includes but is not limited to ITO and FTO.

[0019] The beneficial effects of the present invention are: first, the macromolecular structure of aminoglycoside antibiotics can weaken the adjacent SnO 2 The interaction between nanocrystals promotes the SnO 2 Uniform dispersion of nanocrystals, SnO 2 The particle size is reduced from 13.55 nm to 8.55 nm. The smaller particle size can make the tin dioxide film smoother, which can improve the interface contact between the tin dioxide electron transport layer and the perovskite active layer and reduce interface defects. Aminoglycoside antibiotics can passivate SnO by ionic bonding. 2Defects within the lattice reduce non-radiative recombination and improve charge transfer efficiency. At the interface, the sulfate groups and N containing lone electron pairs can react with the excess Pb in the perovskite. 2+ Coordination can reduce interface defects.

[0020] Second, SnO modified with aminoglycoside antibiotics 2 The electron transport layer film is smoother, which improves the interface contact problem. At the same time, aminoglycoside antibiotics improve the SnO 2 The conductivity of the electron transport layer makes the charge transfer process smoother and the short-circuit current of the device is improved.

[0021] Third, aminoglycoside antibiotics enhance the crystallinity of perovskite and passivate the defects at the interface, which significantly reduces non-radiative recombination. At the same time, the guanidine groups on them can promote the in-plane crystal growth of perovskite, significantly increase the perovskite grain size, and significantly enhance the crystal orientation. The present invention provides an effective solution for the future development of perovskite solar cells. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 a is an atomic force microscope roughness image of a tin dioxide electron transport layer prepared based on the prior art; Figure 1 b is the atomic force microscopy roughness image of the tin dioxide electron transport layer modified with aminoglycoside antibiotics;

[0023] Figure 2 a is an X-ray diffraction pattern of a tin dioxide electron transport layer prepared based on the prior art; Figure 2 b is the X-ray diffraction pattern of the tin dioxide electron transport layer modified with aminoglycoside antibiotics;

[0024] Figure 3 a is a scanning electron microscope morphology image of a tin dioxide electron transport layer prepared based on the prior art; Figure 3 b is a scanning electron microscopy morphology of the tin dioxide electron transport layer modified with aminoglycoside antibiotics;

[0025] Figure 4 a is the short-circuit current and open-circuit voltage curve of the perovskite solar cell with a tin dioxide electron transport layer prepared by the prior art measured under AM1.5G sunlight, Figure 4 b is the short-circuit current and open-circuit voltage curve of the perovskite solar cell based on the tin dioxide electron transport layer modified by aminoglycoside antibiotics;

[0026] Figure 5 This is a structural diagram of the perovskite solar cell prepared by the present invention. DETAILED DESCRIPTION

[0027] Example 1

[0028] Perovskite solar cells based on streptomycin sulfate modified tin dioxide electron transport layer have a planar heterojunction inverse structure: ITO / SnO 2 :Streptomycin sulfate / perovskite absorber / Spiro-OMeTAD / Ag.

[0029] The specific process of preparing the solar cell proposed by the present invention is:

[0030] S1. Pretreatment of the ITO conductive glass substrate: the method is to clean and dry the ITO conductive glass substrate, cool it to room temperature, and then treat the ITO conductive glass substrate with ozone for 15 minutes.

[0031] S2. Spin-coating the aminoglycoside antibiotic-modified tin dioxide precursor solution on the pretreated transparent conductive glass substrate in step S1, and then heat-treating it at 150° C. for 30 min to form an electron transport layer on the transparent conductive glass substrate.

[0032] S21, prepare a tin dioxide precursor solution modified by streptomycin sulfate: Dissolve 7mmol streptomycin sulfate in 1mL deionized water, shake thoroughly to form a uniform and transparent streptomycin sulfate aqueous solution; take another deionized water and add it to the tin dioxide colloidal aqueous dispersion, shake thoroughly to obtain a diluted tin dioxide colloidal aqueous dispersion; the volume ratio of deionized water to the tin dioxide colloidal aqueous dispersion is 4:1; add the streptomycin sulfate aqueous solution to the tin dioxide colloidal aqueous dispersion, shake thoroughly to mix, and obtain a tin dioxide precursor solution modified by streptomycin sulfate. The volume ratio of the streptomycin sulfate aqueous solution to the tin dioxide colloidal aqueous dispersion in the streptomycin sulfate-modified tin dioxide precursor solution is 1:12.

[0033] S22, prepare the electron transport layer: statically spin-coat 100 μL of streptomycin sulfate modified tin dioxide precursor solution on the pretreated ITO conductive glass substrate, the spin coating rate is 4000 r / min, the spin coating time is 30 s; place the spin-coated ITO conductive glass substrate on a heating table for annealing; the annealing temperature is 150°C, the annealing time is 30 min, and a tin dioxide film with a thickness of 30 to 40 nm is formed. S3, spin-coat the perovskite active layer on the surface of the electron transport layer;

[0034] S31, preparation of PbI 2 Solution: 1.3 mol PbI 2 Dissolved in 1 mL of a mixed solvent of DMF and DMSO, with a volume ratio of DMF to DMSO of about 19:1, to obtain PbI 2 Solution;

[0035] S32, prepare a mixed solution of FAI, MABr, and MACl: dissolve FAI, MABr, and MACl in 2 mL of isopropanol solution at a mass ratio of 10:1:1 to form a MACl solution with a concentration of 72 mg / mL. x FA 1-x Br y I z Cl 1-y-z solution, x, y, z are the number of atoms in the molecule; MA x FA 1-x Br y I z Cl 1-y-z The solution was spin-coated on PbI obtained by S31 2 The film is heat treated at 80-120° C. for 10-60 min to obtain a perovskite film.

[0036] S4, spin coating a hole transport material on the surface of the perovskite active layer to obtain a hole transport layer;

[0037] S41, dissolving 540 mg of Li-TFSI in 1 mL of acetonitrile solution, shaking thoroughly, to obtain a Li-TFSI acetonitrile solution; dissolving 720 mg of 2,2,7,7′-tetrakis[N,N′-di(4-methoxyphenyl)amino]-9,9′-spirobifluorene in 1 mL of chlorobenzene, shaking thoroughly, to obtain a 2,2,7,7′-tetrakis[N,N′-di(4-methoxyphenyl)amino]-9,9′-spirobifluorene chlorobenzene solution;

[0038] S42. Sequentially add 18 μL of lithium bis(trifluoromethanesulfonic acid) imide acetonitrile solution and 29 μL of 4-tert-butylpyridine to the 2,2,7,7′-tetrakis[N,N′-di(4-methoxyphenyl)amino]-9,9′-spirobifluorene chlorobenzene solution, and shake thoroughly to obtain a 2,2,7,7′-tetrakis[N,N′-di(4-methoxyphenyl)amino]-9,9′-spirobifluorene mixed solution; S43. Spin-coat the 2,2,7,7′-tetrakis[N,N′-di(4-methoxyphenyl)amino]-9,9′-spirobifluorene mixed solution on the surface of the perovskite active layer at a spin-coating rate of 4000 r / min and a spin-coating time of 30 s to form a hole transport layer.

[0039] S5. Vapor-depositing a metal electrode on the hole transport layer to obtain a perovskite solar cell containing aminoglycoside antibiotic-modified tin dioxide as an electron transport layer, i.e., an aminoglycoside antibiotic-modified tin dioxide perovskite solar cell.

[0040] The test results are as follows:

[0041] Figure 1a is an atomic force microscope roughness image of a tin dioxide electron transport layer prepared based on the prior art; Figure 1 b is an atomic force microscope roughness image of the tin dioxide electron transport layer modified with aminoglycoside antibiotics. Compared with the tin dioxide electron transport layer prepared based on the prior art, the roughness of the tin dioxide electron transport layer modified with aminoglycoside antibiotics is significantly reduced, and the film is more dense and smooth. Smooth SnO 2 The film can improve the interface contact between the electron transport layer and the perovskite layer and reduce interface defects.

[0042] Figure 2 a is an X-ray diffraction pattern of a tin dioxide electron transport layer prepared based on the prior art; Figure 2 b is the X-ray diffraction pattern of the SnO2 electron transport layer modified with aminoglycoside antibiotics; 2 Compared with the perovskite layer above the electron transport layer, the SnO 2 The peak intensity of the perovskite above the electron transport layer at 24.3° is significantly increased, indicating that the crystal orientation of the perovskite is enhanced, which is beneficial to the charge transport inside the perovskite.

[0043] Figure 3 a is a scanning electron microscope morphology image of a tin dioxide electron transport layer prepared based on the prior art; Figure 3 b is a scanning electron microscope morphology of the aminoglycoside antibiotic-modified SnO electron transport layer. 2 Compared with the perovskite layer above the electron transport layer, the SnO 2 The size of the perovskite grains above the electron transport layer is significantly increased, the quality of the perovskite film is higher, and the large-sized perovskite grains are beneficial to improving the optoelectronic performance and stability of the device.

[0044] Figure 4 a is the short-circuit current and open-circuit voltage curve of the perovskite solar cell with a tin dioxide electron transport layer prepared by the prior art measured under AM1.5G sunlight, Figure 4 b is the short-circuit current and open-circuit voltage curve of the perovskite solar cell based on the tin dioxide electron transport layer modified by aminoglycoside antibiotics; compared with the perovskite solar cell with the tin dioxide electron transport layer prepared based on the prior art, the short-circuit current and open-circuit voltage of the perovskite solar cell based on the tin dioxide electron transport layer modified by aminoglycoside antibiotics are significantly improved, and the photovoltaic performance of the device is significantly improved.

[0045] Figure 5 The device structure diagram of the present invention includes an ITO conductive glass substrate, an electron transport layer, a perovskite layer, a hole transport layer and a silver counter electrode from bottom to top.

[0046] Embodiment 2:

[0047] In this comparative example, a method for preparing a perovskite solar cell based on a tin dioxide electron transport layer modified with gentamicin sulfate and kanamycin sulfate was prepared. The difference between this comparative example and comparative example 1 is only that: in the above step S2, the streptomycin sulfate used is replaced by a mixed solution of gentamicin sulfate and kanamycin sulfate, and its formula replacement concentration is the same as that of streptomycin sulfate, and the other steps are basically the same as those in comparative example 1, which will not be repeated here.

[0048] Changing the aminoglycoside antibiotic also improved the PCE of the device, with streptomycin sulfate having the best effect because it contains the richest groups.

[0049] The above descriptions are only individual embodiments of the present invention. It should be pointed out that a person skilled in the art can make several improvements without departing from the principles of the present invention. These improvements are considered to be within the protection scope of the present invention.

Claims

1. An aminoglycoside antibiotic-modified tin dioxide perovskite solar cell, characterized in that: SnO2 modified with aminoglycoside antibiotics is used as an electron transport layer of a perovskite solar cell. The preparation method of the perovskite solar cell is carried out according to the following steps: S1. Pre-treating the transparent conductive glass substrate; S2, spin coating the aminoglycoside antibiotic modified tin dioxide precursor solution on the pretreated transparent conductive glass substrate in step S1, and then heat treating it at 150° C. for 30 min to form an electron transport layer on the transparent conductive glass substrate; the aminoglycoside antibiotic is a mixture of one or more of streptomycin sulfate, gentamicin sulfate, and kanamycin sulfate; S3, spin coating and depositing a perovskite active layer on the surface of the electron transport layer; S4, spin coating a hole transport material on the surface of the perovskite active layer to obtain a hole transport layer; S5. Vapor-depositing a metal electrode on the hole transport layer to obtain a perovskite solar cell containing aminoglycoside antibiotic-modified tin dioxide as an electron transport layer, i.e., an aminoglycoside antibiotic-modified tin dioxide perovskite solar cell.

2. The aminoglycoside antibiotic-modified tin dioxide perovskite solar cell according to claim 1, characterized in that: In step S2, the aminoglycoside antibiotic modified tin dioxide precursor solution is obtained by fully mixing and shaking the aminoglycoside antibiotic aqueous solution and the tin dioxide colloidal aqueous dispersion; wherein the aminoglycoside antibiotic aqueous solution is a solution formed by dissolving 7 mmol of aminoglycoside antibiotics in 1 mL of deionized water, the tin dioxide colloidal aqueous dispersion is formed by uniformly mixing deionized water and tin dioxide colloid in a volume ratio of 4:1, and the volume ratio of the aminoglycoside antibiotic aqueous solution and the tin dioxide colloidal aqueous dispersion is 1:12 when mixed; the aminoglycoside antibiotic modified tin dioxide precursor solution is spin-coated on the pretreated transparent conductive glass substrate in step S1, the spin coating rate is 4000r / min, and the spin coating time is 30s.

3. The aminoglycoside antibiotic-modified tin dioxide perovskite solar cell according to claim 1, characterized in that: In step S3, a two-step spin coating method is used when spin coating the perovskite active layer on the surface of the electron transport layer. The specific steps are as follows: S31, dissolving 1.3 mmol lead iodide PbI2 in 1 mL of a mixed solvent of N, N-dimethylformamide DMF and dimethyl sulfoxide DMSO to prepare a precursor solution, wherein the volume ratio of DMF to DMSO in the mixed solvent of N, N-dimethylformamide DMF and dimethyl sulfoxide DMSO is 19:1, and spin coating the precursor solution on the surface of the electron transport layer at a spin coating rate of 1500 r / min and a spin coating time of 30 s, followed by heat treatment at 70°C for 1 min to obtain a PbI2 thin film; S32, mixing formammonium iodide FAI, methylammonium bromide MABr, and methylammonium chloride MACl in a mass ratio of 10:1:1, and then dissolving them in 2 mL of isopropanol solution to form a MACl with a concentration of 72 mg / mL. x FA 1-x Br y I z Cl 1-y-z solution, x, y, z are the number of atoms in the molecule; MA x FA 1- x Br y I z Cl 1-y-z The solution is spin-coated on the PbI2 film obtained from S31 and heat-treated at 80-120°C for 10-60 min to obtain a perovskite film.

4. The aminoglycoside antibiotic-modified tin dioxide perovskite solar cell according to claim 1, characterized in that: In step S4, spin coating the hole transport material on the surface of the perovskite active layer to obtain a hole transport layer comprises the following steps: S41, dissolving 540 mg of Li-TFSI in 1 mL of acetonitrile solution, shaking thoroughly, to obtain a Li-TFSI acetonitrile solution; dissolving 720 mg of 2,2,7,7′-tetrakis[N,N′-di(4-methoxyphenyl)amino]-9,9′-spirobifluorene in 1 mL of chlorobenzene, shaking thoroughly, to obtain a 2,2,7,7′-tetrakis[N,N′-di(4-methoxyphenyl)amino]-9,9′-spirobifluorene chlorobenzene solution; S42. Sequentially add 18 μL of lithium bis(trifluoromethanesulfonic acid) imide acetonitrile solution and 29 μL of 4-tert-butylpyridine to the 2,2,7,7′-tetrakis[N,N′-di(4-methoxyphenyl)amino]-9,9′-spirobifluorene chlorobenzene solution, and shake thoroughly to obtain a 2,2,7,7′-tetrakis[N,N′-di(4-methoxyphenyl)amino]-9,9′-spirobifluorene mixed solution; S43. Spin-coat the 2,2,7,7′-tetrakis[N,N′-di(4-methoxyphenyl)amino]-9,9′-spirobifluorene mixed solution on the surface of the perovskite active layer at a spin-coating rate of 4000 r / min and a spin-coating time of 30 s to form a hole transport layer.

5. The aminoglycoside antibiotic-modified tin dioxide perovskite solar cell according to claim 1, characterized in that: In step S5, a metal electrode is deposited on the hole transport layer. The metal electrode material is Ag, Au or Al. A vacuum coating machine is used to deposit a silver electrode on the surface of the hole transport layer using a conventional thermal evaporation process. The evaporation rate is 0.1 nm / s and the area of ​​the metal electrode is 0.04 cm 2 .

6. The aminoglycoside antibiotic-modified tin dioxide perovskite solar cell according to claim 1, characterized in that: The thickness of the electron transport layer is 30-40 nm, the thickness of the perovskite active layer is 480-500 nm, the thickness of the hole transport layer is 150-180 nm, and the thickness of the metal electrode is 100 nm.

Citation Information

Patent Citations

  • Protected donor electrodes for electro-transport drug delivery

    US20090069740A1

  • Water treatment

    WO2020223824A1